Stability problems in the hydrogen production by dark fermentation: Possible causes and solutions - Castelló, Elena; Nunes Ferraz-Junior, Antonio Djalma; Andreani, Cristiane; Anzola-Rojas, Melida del Pilar; Borzacconi, Liliana; Buitrón, Germán; Carrillo-Reyes, Julián; Gomes, Simone Damasceno; Maintinguer, Sandra I. [UNESP]; Moreno-Andrade, Iván; Palomo-Briones, Rodolfo; Razo-Flores, Elías; et al. (Elsevier, 2020)
H2 production by dark fermentation using mixed cultures has been studied intensively during the last two decades, and its feasibility has been demonstrated. Different substrates, operational conditions, and reactor technologies have been widely studied and there is a general agreement that the use of non-sterile fermentable substrates is required to make the process feasible for scaling up. Nonetheless, stability problems during long term operation may hinder its application at large scale. This work, written by members of the Latin American Biohydrogen Network, analyse and discuss instability causes and possible solutions in the H2 production by dark fermentation. It is concluded that instability is mostly linked to the biotic aspects of the process (i.e., changes in the microbial community composition, presence of organisms that consume hydrogen and compete for the substrate, and accumulation of fermentation products); regardless of the reactor configuration. However, some problems like excessive growth of microorganisms and methanogens presence were mostly reported in fixed bed reactors and granular sludge reactors. The novelty of this work relies on the comprehensive revision of the main causes behind the unstable and low hydrogen production and how these causes are linked to the technology used. The strategies to overcome the problems as well as the potential implications are also analysed.
Keywords: Biohydrogen production; Dark fermentation; H2 production microbiology; Homoacetogenesis; Lactic acid bacteria; Unstable H2 production